EFFECT OF INORGANIC FERTILIZERS AND PRESSMUD COMPOST ON SOIL PROPERTIES, YIELD AND QUALITY OF BHENDI - A. ANGAYARKANNI, P. POONKODI; A. BALAKUMAR, R. VIJAYAKUMAR (Journal of Ecobiotechnology, 2018)
A field experiment was conducted at farmer`s field in Sivapuri village, Chidambaram taluk, Cuddalore district, Tamil Nadu to study the effect of inorganic fertilizers and pressmud compost on soil properties, yield and quality of bhendi cultivar Arka anamika as a test crop. The experimental soil was sandy clay loam with a pH of 7.20, EC of 0.64 dSm-1 and CEC of 19.20 c mol (p+) kg-1. The results of the experiment clearly revealed that the application of 100% recommended dose of fertilizer+15 tonnes of pressmud compost ha-1 (T4) registered the maximum fruit and stover yield of bhendi the same treatment T4 improved the quality attributes of bhendi viz., crude protein content, ascorbic acid content and crude fibre content. The available N, P, K and S content in the post harvest soil was maximum in the treatment T4. This treatment was followed by application of 75% recommended dose of fertilizer+15 tonnes of pressmud compost ha-1 (T7) regarding yield and quality attributes, as well as available nutrients status of post harvest soil. However, these two treatments were comparable to each other.